Comparison of Volatiles Profile and Contents of Trichothecenes Group B, Ergosterol, and ATP of Bread Wheat, Durum Wheat, and Triticale Grain Naturally Contaminated by Mycobiota - Buśko, Maciej; Stuper, Kinga; Jeleń, Henryk; Góral, Tomasz; Chmielewski, Jarosław; Tyrakowska, Bożena; Perkowski, Juliusz (Frontiers in Plant Science, 2016)
In natural conditions cereals can be infested by pathogenic fungi. These can reduce the grain yield and quality by contamination with mycotoxins which are harmful for plants, animals and humans. To date, performed studies of the compounds profile have allowed for the distinction of individual species of fungi. The aim of this study was to determine the profile of volatile compounds and trichothecenes of group B, ergosterol, adenosine triphosphate content carried out on a representative sample of 16 genotypes of related cereals: triticale, bread wheat and durum wheat. Based on an analysis of volatile compounds by means of gas chromatography mass spectrometry and with the use of an electronic nose, volatile profiles for cereals were determined. Differentiation is presented at four levels through discriminant analysis, heatmaps, principal component analysis (PCA) and electronic nose maps. The statistical model was built by subsequent incorporation of chemical groups such as trichothecenes (GC/MS), fungal biomass indicators (ergosterol (HPLC) and ATP (luminometric) and volatiles. The results of the discriminatory analyses showed that the volatile metabolites most markedly differentiated grain samples, among which were mainly: lilial, trichodiene, p-xylene. Electronic nose analysis made it possible to completely separate all the analyzed cereals based only on 100 ions from the 50-150 m/z range. The research carried out using chemometric analysis indicated significant differences in the volatile metabolites present in the grain of bread wheat, durum wheat and triticale. The end result of the performed analyses was a complete discrimination of the examined cereals based on the metabolites present in their grain.